1974
DOI: 10.2151/jmsj1965.52.6_457
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dust on Radiation Transfer in the Martian Atmosphere (I)

Abstract: The equations of infrared radiation transfer are numerically solved for the Martian atmosphere, with consideration of the effect of dust, which absorbs, emits and scatters light. Primary mineral constituent of dust, we assumed, is quartz. Three cases on dust concentration are considered : the first corresponds to a heavy dust storm event, the second to a dusty case and the third to out-of-storm case. From the solutions obtained by the method of an iterative numerical integration, radiative heating or cooling r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…There are several indications that a fairly large amount of dust is suspended in the Martian atmosphere, not only at the time when a great dust storm event occurs but also during ordinary conditions. Recent observations by space probes and recent theoretical studies [e.g., Moriyama, 1974Moriyama, , 1975Zurek, 1978] have led us to investigate the effect of dust on the atmospheric general circulation. A strong tidal forcing in the Martian atmosphere would be mainly caused by direct absorption of the solar radiation owing to dust.…”
Section: Introductionmentioning
confidence: 99%
“…There are several indications that a fairly large amount of dust is suspended in the Martian atmosphere, not only at the time when a great dust storm event occurs but also during ordinary conditions. Recent observations by space probes and recent theoretical studies [e.g., Moriyama, 1974Moriyama, , 1975Zurek, 1978] have led us to investigate the effect of dust on the atmospheric general circulation. A strong tidal forcing in the Martian atmosphere would be mainly caused by direct absorption of the solar radiation owing to dust.…”
Section: Introductionmentioning
confidence: 99%
“…In our analysis we neglect the impact of CO 2 on atmospheric heating and cooling rates. The CO 2 absorbs only 1% of solar radiation, producing cooling and heating rates around 4 -5 K/day when sun is in zenith (Moriyama, 1974;Savijarvi et al, 2005). The trace gases have also a negligible effect on heating and cooling rates when compared to dust.…”
Section: Heating and Cooling Rates For Selected Measurements During H...mentioning
confidence: 99%
“…Our results are in good agreement with previous theoretical calculations. Moriyama (1974) showed that in lower portion of dust layers, cooling due to the IR radiation of dust becomes one of the most predominant term in heat budget. In dusty atmospheres, cooling rates of 60-80 K/days can be observed close to the surface (Moriyama, 1974).…”
Section: Moriyamamentioning
confidence: 99%
“…The thermal tide is likely to be strongly related with the thermal effects due to dust. Absorption of solar radiation due to dust is also a very important term as energy source of atmospheric motion (Gierasch and Goody, 1973;Golitsyn, 1973;Hess, 1973: Leovy et al, 1973 In the previous paper (Moriyama, 1974), we studied the effect of dust on infrared radiation transfer, and pointed out its importance to the thermal structure of the Martian atmosphere. As an extension of our study on radiative effects of dust, now we investigate quantitatively heating of the Martian atmosphere due to absorption of the visible solar radiation in the present paper.…”
Section: Introductionmentioning
confidence: 99%